Antitumor Effects of Madu Lebah Tualang on Human Leukemia Cell Line (K562) - Hassan, Rosline (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Tualang Honey possesses as therapeutic potential in wound healing, antimicrobial activity and antiproliferative against several cancer model such as Oral Squamous Cell Carcinomas (OSCC), Human Osteosarcoma (HOS), human breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cell lines. The aim of this study was to evaluate the apoptosis effect of natural local honey “Tualang Honey" on leukemia cell line. In order to evaluate this effect, leukemia cell line (K562) and normal mononuclear cell isolate from peripheral blood were grown in RPMI 1640 culture medium. Both cell lines were incubated with increasing concentrations of Tualang Honey for 24 hours at 37°C. After incubation, they were evaluated for cytotoxicity and apoptotic activity. The IC 50 value against K562 cell line was determined at 0.6% (18ul) after 24 hours. Apoptosis was seen in both K562 and mononuclear cell after incubation with Tualang Honey. However the percentage of apoptosis was much higher with K562 compared to mononuclear cell. At the concentration of IC50 (0.6%>), Tualang Honey gave the 53.9°% apoptosis activity to K562, as opposed to mononuclear cell (37.4°%) (p<0.05). Therefore Tualang Honey is shown to be a potential anti-leukemic substance.